INTELLIGENT TECHNOLOGIES OF STRATEGIC AND OPERATIVE MANAGEMENT SUPPORT FOR ENTERPRISES - Chornous, Galyna O. (Ekonomika, 2014)
Abstract. The article is devoted to the development of a mechanism for the proactive support of strategic and operational decision-making in an enterprise. The starting point for this mechanism should be a model (pattern) of the enterprise, which embodies the principles of balanced strategic measurement systems. Development of the enterprise pattern as an ‘object–project–process–environment’ configuration allows to stitch together the strategic and operational indicators, to provide a vertical continuity, the allocation of responsibilities for the purpose of full control. An effective use of the enterprise data as a strategic resource involves knowledge discovery for decision support through developing interrelated analytical models. Taking into account the limitations of classical methods for strategic and operational management support, Data Mining (DM) is proposed as an adequate modeling tool. A basic set of autonomous DM methods for developing appropriate models is proposed. Besides, it is demonstrated that an effective mechanism for decision support should be based on the application of hybrid intelligent models and methods, and should be brought up to the level of a hybrid decision support system DSS. Achievements of modern information technology (Big Data, analytics in memory, cloud technology, etc.) play in favor of the proposed approach. Key words: strategic management, operative management, intelligent technologies, mechanism for decision support, DSS